Socialization of Osteoporosis Prevention Exercise and Covid-19 Vaccination Education - I Gusti Ayu Rai Widowati; Ida Ayu Ratih Wulansari Manuaba; Ida Ayu Manik Partha Sutema (UNUSA Press, 2022)
Gymnastics prevention for osteoporosis is a combination of several exercises with various benefits. Exercises such as low-impact aerobics, which helps improve heart and lung fitness, weight-bearing exercise to increase bone density, resistance to increase muscle strength and bone density, as well as coordination and balance which are beneficial to reduce the risk of falls and fractures. Community Service by the Association of Indonesian Healthy Bone Citizens (PERWATUSI) of Bali Province collaborates with the Clinical Pharmacy and Physiotherapy Study Program at the University of Bali International to educate the general public. The education regarding knowledge, beliefs, and appropriate exercise practices to prevent the early occurrence of osteoporosis and efforts to improve the immunity system for the Covid 19 vaccination preference. The service method is carried out by socializing and practicing gymnastics in the field, followed by discussions and questions and answers with a resource person. During this study, approximately 50 public communities were enrolled. The activity went smoothly and was supported by outstanding attention from the participants. The implementation of community service with various parts needs to be intensified to provide benefits to improve the health status of the community.